Analisis Performansi Rantai Pasok Keripik Kentang pada UD. Rimbaku di Kota Batu dengan Metode Supply Chain Operation Reference (SCOR) - Purwaningrum, Novita; Amir, Nur Ocvanny (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Potato chips are one of the fastest growing businesses. Batu City has great potential in developing the potato chips business. One of the industries that runs a potato chips in business in Batu City in UD. Rimbaku. Although it has been along time since establishing a potato chips business, UD. Rimbaku still expriensces several problems in managing the supply chain such as the availability of raw materials, dependence on supplier and production delays. The purpose of this study is 1) to determine the flow of the supply chain at UD. Rimbaku 2) to analize the performance of the potato chips supply chain at UD. Rimbaku using the Supply Chain Operation Reference (SCOR) method 3) to determine the priority of improving the performance of potato chips supply chain at UD. Rimbaku using the Analitycal Hierarchy Process (AHP) method. Respondents were taken using the Snowball Sampling method. Performance analysis using the SCOR method. Supply chain weighting using the AHP method with Expert Choice Software. The result of this study shows 1) the flow of potato chips products moves from upstream to downstream or from potato suppliers to UD. Rimbaku then to retail and finally to consuments, the flow of money moves in the opposite direction from consumers to supplier farmers, the flow of information thet occurs flows in two directions, 2) the performance of UD. Rimbaku's supply chain using the SCOR method gets a value of 95%, including in the very good category, and 3) priority for improving supply chain performance based on AHP, namely make, reliability in the make process and adherence to production schedule.